The impact of geographic indication recognition on farmers’ intentions for green production behavior: a case study of Gannan navel oranges in China - Liu, Qiong; Lu, Hua; Shi, Xinyi (Frontiers in Sustainable Food Systems, 2025)
Geographical indication of agricultural products is not only a distinct symbol of local characteristic agriculture, but also a powerful engine for promoting high-quality agricultural development and facilitating rural revitalization. Exploring the mechanism by which farmers’ cognition of geographical indications affects their willingness for green production can help identify the fundamental path to maintaining the unique qualities of geographical indication agricultural products at the farmer level. Drawing upon the theory of planned behavior, this study establishes a theoretical framework of the impact of farmers’ geographical indication cognition on their willingness to engage in green production. Using the survey data collected from farmers in Xinfeng and Anyuan counties of Jiangxi Province, China, and the structural equation modeling to test the theoretical model, the conclusions are as follows: (1) Farmers’ attitudes towards green production, perceived behavioral control, and subjective norms significantly affect their intentions to adopt green production practices. Among these, the attitude towards green production has the most substantial impact, followed by subjective norms and perceived behavioral control. (2) Additionally, farmers’ geographical indication cognition directly positively influences their willingness to implement green production. (3) This cognition also positively influences their behavioral attitude, behavioral control, and subjective norm regarding green production, thereby indirectly shaping their green production behavioral intention, and the influence is ranked as follows: behavioral attitude, subjective norm, and behavioral control.